What Worked?: policy mobility and the public health approach to youth violence, 2021-2023 - Fraser, Alistair David (UK Data Service, 2024)
he What Worked? Policy Mobility and the Public Health Approach to Youth Violence study sought to further the ESRC's strategic objective of a 'safer, fairer society' through establishing a new evidence-base on public health approaches to violence reduction, and the ways such policies transfer between jurisdictions, to shape policy, guide best practice, and inform academic and public debate. Its main aim was to respond to the urgent social problem of rising youth violence. England and Wales have seen marked increases in homicide, knife crime, and hospital admissions for stab wounds, with particular concentrations in the city of London. Cressida Dick, when Commissioner of the Metropolitan Police, stated that tackling youth violence was her 'number one priority.' In March 2019, UK Prime Minister Theresa May unveiled a consultation on a new public health strategy for youth violence. This approach, which seeks to address violence using principles of prevention and education rather than policing and justice, marks a major step-change in policy. The interest in developing this approach stems primarily from Scotland, where radical reductions in violent crime over the last decade have been attributed to the adoption of a public health model. There was however a lack of clear understanding of 'what worked' in the Scottish context. While there have indeed been marked declines in youth violence, the mechanisms that have driven this decrease are poorly understood. There is confusion over what public health approaches are, how they work, and the conditions under which such ideas can travel. As a result, despite significant potential, the implications of the public health approach remain vague. This study was delivered in a three work-streams approach, over a three-year period: 1. What Worked - Through interviews with elite actors/professionals - senior police, politicians, and civil servants - the research team aimed to establish an expert appraisal of the causes of violence reduction in Scotland. This was complemented by a detailed documentary analysis, investigating the social, political, and cultural conditions in which violence reduction occurred, and a series of 20 semi-structured interviews with practitioners and residents of communities affected by violence to establish a 'bottom-up' account of change. Finally, available statistical data on violence and health was leveraged to triangulate explanations. These data sources were combined to produce a policy briefing, two journal articles, and a short film on the theme of 'what worked'. 2. Policy Travels - Using flexible and responsive ethnographic methods, the research team aimed to track the evolution of the public health approach in London as it evolved in real-time, entering the 'assumptive worlds' of policy through attendance at key meetings and events. Observations were complemented by a series of semi-structured interviews with elite actors engaged in violence reduction in London, and 20 semi-structured interviews with residents and youth practitioners, exploring the factors that promote or impede change. Mirroring data-collection in Scotland, relevant statistical data was used to evaluate the extent to which policy changes are impacting on violence reduction. These data were used to produce a second policy briefing, two journal articles, and a series of podcasts on 'how ideas travel'. 3. Connecting Communities - Data from these work-streams will be connected via an open access data set to enhance understanding of best practice in violence reduction. Data will be analysed and published as an academic monograph aimed at scholars working in the areas of criminology, public health and social policy. Through our advisory group and engagement with policy user-groups, the research team will engage directly with policy actors at the highest level, and using cooperative methods will create a practitioner toolkit. Communities of policy, practice and public will be connected through a website, a series of events and a roadshow. - The UKDS study currently includes 127 qualitative interview transcripts, drawn from policy-makers and community participants. See the 'Data List' in the documentation for more details.